Juridical Analysis of the Role of the Prosecutor’s Office in Criminal Law - Yohanes Pande; Riadi Asra Rahmad; Yanto Irianto; Rio Akmal Syahban; Sy Muhammad Ridho Rizki Maulufi Alkadrie (Universitas Muhammadiyah Palu, 2024)
Basically, the Prosecutor's Office is a state law enforcement tool, protector and protector of society, obliged to maintain the rule of law. The Prosecutor's Office thus acts as a law enforcer. The prosecutor's office is the only state institution which is a government apparatus that has the authority to delegate criminal cases, prosecute perpetrators of criminal acts in court and carry out decisions and decisions of criminal judges. This power is a characteristic of the prosecutor's office that differentiates other law enforcement institutions or bodies. In the criminal justice system, there is a prosecution sub-system carried out by the Prosecutor's Office of the Republic of Indonesia. The prosecutor has an important role in the trial and it is the prosecutor who is authorized by law to carry out prosecutions as a public prosecutor who acts on behalf of the State in carrying out his duties and authority. In the realm of criminal law, the prosecutor's office has a very urgent role and also has a role and authority which is confirmed in Article 30C of Law Number 11 of 2021 concerning Amendments to Law Number 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia.